Act Alike & Think Alike Historians: Arguments on Academic History, Collective Memory & Contemporary Studies - Naeem, Hafiz Muhammad; Hussain, Nazia Munazer (Advances in Social Sciences Research Journal, 2015)
For learning history we need two significant things to start, one research and other is educational role. The basic purpose of learning historical education, with the help of above said technological perspective, is to develop figures, texts, artifacts, historical accounts as secondary resource. As per this learning rule if historical accounts have significant important for student to get knowledge about history then educational institutes should make it as obvious education aim. Some researchers also suggested that students should also spend time to do meaningful historical researches (if historical narratives are available) rather than to study primary sources regularly. In this review paper, I would explain debatable approaches that will explain the usage of historical support for the students to develop their understanding in conducting valuable researchers and quality education. For better indulgent, this report will help to understand the role of educational resources in developing understanding and completion of historical based research while taking experiences, academicians and collective memory history into consideration.